Morphological Aspects of Oral Denticles in the Sharpnose Shark Rhizoprionodon lalandii (Muller and Henle, 1839) (Elasmobranchii, Carcharhinidae) - Ciena, A. P. [UNESP]; Rangel, B. de S.; Bruno, C. E. M.; Miglino, M. A.; Amorim, A. F. de; Rici, R. E. G.; Watanabe, I. (Wiley-Blackwell, 2016)
The oral denticles of some elasmobranchs are found on the surface of the oral cavity and are homologous to those on the body surface, being well developed, independent and non-growing, with varying morphology and distribution depending on the species. The structural and three-dimensional characteristics of oral denticles from the rostro-ventral surface of the sharpnose shark Rhizoprionodon lalandii were described following imaging by both light and scanning electron microscopy. The light microscopy results showed that the triangular shape of the denticles consisted of a base and an apex. Picrosirius staining showed the arrangement of collagen fibres and oral denticles, and a predominance of type-I collagen was found in both structures under polarized light. There was a broad homogeneous distribution of denticles on the ventral surface, forming a leaf-like shape with the cusp facing the caudal region. Interlocking, hexagonal, geometric structures on its rostral side and ridges on the rostral side of the oral denticles were observed under increased magnification. We concluded that the denticle morphology found in R. lalandii differ of others analysed species, and the descriptions of these structures therefore provide important information for the classification of the species. In this species, the main functions can be assigned to help reduce hydrodynamic drag, particularly by this being a species that uses ram ventilation, and to protect the epithelium of the oropharynx of abrasion and parasites.